(untitled) (Journal of Medicine, 2025)
A 58-year-old male presented with complaints of new-onset periodic tremors and spasms for a few days. The patient was found to have recently started a course of trimethoprim-sulfamethoxazole (TMP-SMX) due to concern for a suspected urinary tract infection found incidentally after presenting for wound dehiscence following L1-L4 laminectomies a month prior. A neurological workup revealed was unremarkable, resulting in the exploration of further potential causes. A literature review revealed a case report that reported myoclonus as an adverse effect of TMP-SMX. So, the medication was discontinued, resulting in a resolution of myoclonus. The purpose of this case report is to make clinicians aware of a rare reversible adverse drug reaction from the use of TMP-SMX. J MEDICINE 2025; 26: 77-79